Student’s Digital Law Knowledge About Hoax: Study at SMA Batik 2 Surakarta - Wulandari Wulandari; Rini Triastuti; Dewi Gunawati; Laksmi Evasufi Widi Fajari (International Journal of Asian Education, 2022)
The development of this modern era requires every human being to be fluent in technology. There are so many positive sides to technology that humans can get. Nevertheless, there is also a negative side to the existence of technology. One of them is the growing number of crimes in cyberspace. Hoax is one of the crimes committed in cyberspace. This study describes the digital legal knowledge of students about Hoaxes. This study used a sample of 206 students at SMA Batik 2 Surakarta. This research uses qualitative research methods with purposive sampling techniques. Data were taken using interviews, observations, and questionnaires. The results showed that students were digital citizens, and their digital legal knowledge about hoaxes was still lacking. Citizenship Education is one of the subjects in schools that can teach legal provisions regarding hoaxes. Policy recommendations that can be given are as follows, (1) Teachers can use various interactive learning models where students can actively seek and understand the legal provisions regarding hoaxes. In addition, the teacher must also be active and creative in linking the subject matter with legal regulations regarding hoaxes. (2) The government must always improve the curriculum’s content to develop according to the needs of students in the present.